Hydraulic Conductivity and Waste Contaminant Transport in Soil 1994
DOI: 10.1520/stp23890s
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Testing to Evaluate Changes in Hydraulic Conductivity of Compacted Clays Caused by Freeze-Thaw: State-of-the-Art

Abstract: Several laboratory studies have shown that the hydraulic conductivity of compacted clay may increase up to three orders of magnitude when subjected to freeze-thaw. In this paper, methods to freeze and thaw specimens of compacted clay are reviewed and compared. Methods to measure the hydraulic conductivity of the specimens are also reviewed. Only naturally formed clay soils are considered; soil-bentonite mixtures and other amended soils are not included. A review of testing conditions present dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The ultimate minimum temperature reached during the subzero portion of the freeze-thaw cycle therefore becomes an important consideration because this, along with the pore geometry, largely controls the proportion of pore water actually freezing. Othman et al ( 1994) found greater increases in the hydraulic conductivity of thawed clays when a minimum freezing temperature of -2°C was used rather than -1°C. Large variation in the data from the -1°C tests also suggested that a large portion of the pore water might have remained unfrozen.…”
mentioning
confidence: 86%
“…The ultimate minimum temperature reached during the subzero portion of the freeze-thaw cycle therefore becomes an important consideration because this, along with the pore geometry, largely controls the proportion of pore water actually freezing. Othman et al ( 1994) found greater increases in the hydraulic conductivity of thawed clays when a minimum freezing temperature of -2°C was used rather than -1°C. Large variation in the data from the -1°C tests also suggested that a large portion of the pore water might have remained unfrozen.…”
mentioning
confidence: 86%
“…For instance, in closed-system freezing, drainage is closed and no additional water enters the sample, whereas in open-system freezing, water from an external source is available and, depending on the frost susceptibility of the soil tested, it may be attracted to the freezing front and form significant ice lenses. Othman et al (1993) reported little effect on the hydraulic conductivity changes of thawed clays frozen with or without access to an external water source.…”
Section: Previous Studiesmentioning
confidence: 92%
“…Othman et al (1994) observed significant increase in the hydraulic conductivity of compacted clay (two to three orders of magnitude) within three to five freeze -thaw cycles. Similar phenomena were observed on soft fine-grained soils (Eigenbrod 1996) and in a small-scale field test (Benson and Othman 1993).…”
Section: Introductionmentioning
confidence: 90%